Toxicological Effects of Crude Oil: Integrated Biomarker Responses in the Hepatopancreas of Clam Ruditapes philippinarum - Xia, Bin; Chen, Bijuan; Sun, Xuemei; Cui, Yi; Zhao, Jun; Qu, Keming (Asian Journal of Chemistry, 2014)
A battery of biomarkers, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferases (GST) and peroxidase (POD) in hepatopancreas, were measured to test the toxicological effects of the water-soluble fraction of crude oil on clam (Ruditapes philippinarum) for period of 1, 2, 4, 8 and 15 days. The results showed that these biomarker responses exhibited a certain dose-effect and time-effect relation. Subsequently, the enzymatic activities were quantified using the integrated biomarker response method. In short-term exposure (1, 2 and 4 days), the superoxide dismutase and catalase (maximum values of integrated biomarker response) were the dominant enzymes. Furthermore, the integrated biomarker response values were well correlated with the concentrations of petroleum in short-term exposure (r2 = 0.521, 0.815 and 0.935 for 1, 2 and 4 days, respectively). These results suggest that the integrated biomarker response approach may be a useful tool to evaluate the sub-lethal effects of petroleum hydrocarbons on marine organism in short-term exposure.